2013
DOI: 10.1007/s00339-013-7817-x
|View full text |Cite
|
Sign up to set email alerts
|

Defect-mediated ferromagnetism in ZnO:Mn nanorods

Abstract: In this work, the structural, chemical and magnetic properties of ZnO:Mn nanorods were investigated. Firstly, well-aligned ZnO nanorods with their long axis parallel to the crystalline c-axis were successfully grown by the vapor phase transport technique on Si substrates coated with a ZnO buffer layer. Mn metal was then diffused into these nanorods at different temperatures in vacuum. From SEM results, ZnO:Mn nanorods were observed to have diameters of ~100 nm and lengths of 4 µm. XPS analysis showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Therefore, a great density of native defects in conjunction with Mn doping helps to produce more BMPs which yields a greater overall volume occupied by BMPs, leading to the overlap of BMPs, resulting in ferromagnetism. 5) Some groups' results well agree with BMP model, they found that the ferromagnetism of their samples became stronger with the increase of the concentration of V o 19,[29][30][31] and the Mn nearest neighbour short range exchange interaction (ferromagnetic=antiferromagnetic) is strongly dependent on the concentration of structural defects. 19,32) Since in our study, the result shows that the sample which gets minimum V o concentration is found to be stronger ferromagnetism, the BMP model is not fitted.…”
Section: Resultssupporting
confidence: 61%
“…Therefore, a great density of native defects in conjunction with Mn doping helps to produce more BMPs which yields a greater overall volume occupied by BMPs, leading to the overlap of BMPs, resulting in ferromagnetism. 5) Some groups' results well agree with BMP model, they found that the ferromagnetism of their samples became stronger with the increase of the concentration of V o 19,[29][30][31] and the Mn nearest neighbour short range exchange interaction (ferromagnetic=antiferromagnetic) is strongly dependent on the concentration of structural defects. 19,32) Since in our study, the result shows that the sample which gets minimum V o concentration is found to be stronger ferromagnetism, the BMP model is not fitted.…”
Section: Resultssupporting
confidence: 61%